Cost accounting - Boyd, Ken (--For dummies., 2022)
Take control of overhead, budgeting, and profitability with cost accounting Cost accounting is one of the most important skills in business, and its popularity as a course in undergraduate and graduate business and management programs speaks to its usefulness. But if you've ever felt intimidated by the subject's jargon or concepts, you can stop worrying. Cost accounting is for everyone! In Cost Accounting For Dummies, you'll be taken step-by-step through the basic and advanced topics found in a typical cost accounting class, from how to define costs and how to allocate them to products or services. You'll learn how to determine if a capital expenditure is worth it and how to design a budget model that forecasts changes in costs based on activity levels. Whether you're a student in your first cost accounting course or a professional trying to get a grip on your books, you'll benefit from: Simple methods to evaluate business risks and rewards Explanations of how to manage and control costs during periods of business change and pivots Descriptions of how to use cost accounting to price IT projects Cost Accounting For Dummies is the gold standard in getting a firm grasp on the challenging and rewarding world of cost accounting.